Method for exposing carbon fibers on composite bipolar plates. (15th December 2015) - Lee, Dongyoung; Lim, Jun Woo; Nam, Soohyun; Choi, Ilbeom; Lee, Dai Gil
Abstract: The carbon/epoxy composite bipolar plate is an ideal substitute for the brittle graphite bipolar plate for proton exchange membrane fuel cells (PEMFCs) and vanadium redox flow batteries (VRFBs) because of its high mechanical properties and easy manufacturing. However, due to the resin-rich area that forms on its surface, the carbon/epoxy composite bipolar plate requires an expanded graphite coating to decrease the areal specific resistance (ASR). The expanded graphite coating not only increases the manufacturing costs but also has very low mechanical properties. In this work, an innovative manufacturing method that exposes carbon fibers on the surface of the carbon/epoxy composite bipolar plate was developed. Soft release films were inserted between the mold and the composite to prevent the formation of a resin-rich area and to expose carbon fibers on the surface of the bipolar plate. The developed method considerably decreased the ASR of the carbon composite bipolar plate without an expanded graphite coating, which satisfied the target established by the Department of Energy (DOE) of United States. The effects of the soft layer on the mechanical and electrical properties of the carbon composite bipolar plate were investigated.